Identification of the Powdery Mildew Resistance in Chinese Wheat Cultivar Heng 4568 and its Evaluation in Marker-Assisted Selection - Gao, Huiming; Xu, Xiaozhe; Ai, Pengfei; Luo, Fuyi; Guo, Peng; Ma, Pengtao (Frontiers in Genetics, 2022)
Powdery mildew induced by Blumeria graminis f. sp. Tritici (Bgt) has a devastating impact on global wheat yield and quality. Host resistance is the most effective and economical means to control this disease. In this study, Heng 4568, an elite wheat cultivar, shows high resistance to 12 Bgt isolates from different regions in China at the seedling stage. Genetic analysis demonstrates that the powdery mildew resistance in Heng 4568 is conferred by a single dominant locus, temporarily designated PmH4568. Furthermore, PmH4568 is mapped to the reported Pm2 interval on chromosome 5DS with five Pm2 linked markers and flanked by the markers Bwm20 and Bwm21 with a genetic distance of 0.3 and 0.6 cM, respectively. To further investigate the relationship between PmH4568 and Pm2, the diagnostic marker Pm2b-map-3 of Pm2 is used to genotype the F2:3 population derived from the cross Heng 4568 × Daimai 2173. Notably, there is no recombination found, indicating that PmH4568 is also probably a Pm2 allele. In addition, five closely linked markers as well as one diagnostic marker are successfully developed and tested in 16 wheat cultivars from different agro-ecological areas in China, which have potential applications in molecular breeding by marker-assisted selection.